The Influence of Type 2 Diabetes Mellitus Education on Elderly Knowledge in the Pejaten Timur Subdistrict Area, South Jakarta - Teti Hayati; Wilda Fauzia; Ana Khumaeroh; Imam Subiyanto (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
Education is one of the pillars of managing diabetes mellitus, one of which is type 2 diabetes mellitus which is experienced by many diabetics. This study aims to determine the effect of type 2 diabetes mellitus education on the knowledge of M.T Hubbi Arrassuul's mother at RW. 01 Pejaten Timur Jakarta. This research method is a quasy experiment with one group pre-post design. The results of the study showed that knowledge increased after educational interventions with a p value of 0.000. The conclusion of this study is that education can help prevent type 2 diabetes mellitus by increasing knowledge about diabetes mellitus.